The Challenges of Cardiac Resynchronization Therapy in Patients with Dilated Cardiomyopathy and Persistent Left Superior Vena Cava: A Case Report and Concise Literature Review - Silvius Alexandru Pescariu; Raluca Șoșdean; Monica Nicoleta Mircea; Adina Ionac; Sorin Pescariu (Biomedicines, 2023)
Heart failure with reduced ejection fraction (HFrEF) is a chronic and debilitating disease, which requires extensive diagnostic and treatment resources in order to achieve an acceptable quality of life for the patient. While optimal medical treatment remains at the core of the disease’s management, interventional cardiology also plays a very important role. However, in very rare situations, interventionists might find cases especially challenging due to the presence of venous anomalies, such as persistent left superior vena cava (PLSVC), anomalies that may go undiscovered during the patient’s lifetime until venous cannulation is necessary. While these types of malformations also pose challenges in regards to standard pacemaker implantation, cardiac resynchronization (CRT) devices pose several additional challenges due to the complexity of the device and the necessity of finding an optimal position for the coronary sinus (CS) lead. We present the case of a 55-year-old male patient with advanced heart failure due to dilated cardiomyopathy (DCM) and LBBB who was a candidate for CRT-D therapy, describing the investigations that led to the discovery of the PLSVC as well as the technique and results of the intervention, while comparing our case to similar cases found in recent literature.